How viewing objects with the dorsal or ventral retina affects colour-related behaviour in guppies (Poecilia reticulata). (May 2019) - Sibeaux, Adélaïde; Keser, Madison L.; Cole, Gemma L.; Kranz, Alexandrea M.; Endler, John A.
Abstract: Visual pigments can vary across the retina in many vertebrates, but the behavioural consequences of this retinal heterogeneity are unknown. Guppies ( Poecilia reticulata ) vary dorsoventrally in visual pigments and forage both on the ground and at the water surface, exposing different retinal regions to two very different visual environments. We tested guppy behaviour towards a moving stimulus presented below or above the guppy. We used 12 different narrow-band wavelength stimuli matching each of the opsin peak sensitivities presented either at the top or the bottom of our experimental apparatus. We analysed behaviours of 50 male and 50 female guppies over 4800 trials where a moving stimulus pattern was presented to each guppy. We found that wavelength, position and speed of the stimuli influenced male and female behaviour and seems to be mediated by the long wavelength sensitive photoreceptors. Males also had stronger behavioural responses than females whereas females performed more foraging-related pecking behaviour. Our results suggest that the spatial requirement of visual tasks and their ecological context are important and appear to be partly correlated with photoreceptor arrangement in the retina.